Application of Project-Based Learning Model in Speaking Skill Learning Grade 9 at Madrasah Tsanawiyah Negri 2 Mojokerto | Penerapan Model Pembelajaran Berbasis Proyek Dalam Pembelajaran Maharah Kalam Kelas 9 di Madrasah Tsanawiyah Negri 2 Mojokerto - Indrawati, Ninik; Maulana, Muhammad Roqi (NAJAH BESTARI, 2024)
In education, it is important to utilize the central role of language to support students' intellectual and social development. Thus, language learning becomes more effective and can increase student success in various aspects of learning. In Class Arabic learning activities still focus on reading and memorizing texts monotonously and purposefully without the application of the ability to speak Arabic itself, and there are still many students who have difficulty in pronouncing Arabic correctly. This study aims to describe the planning and application of the Project-Based Learning Model and the constraints experienced by students' abilities, especially in the field of speaking. In this study using a descriptive qualitative research approach, by collecting some data from: observations, interviews, documentation and other supporting documents. The results showed that the process of planning a project-based learning model in maharah kalam learning in class IX MTsN 2 Mojokerto was divided into 2 stages. Then the application of the model for one week with several stages that have been structured so as to produce a product that will be presented by each group using Arabic. The obstacles experienced are the implementation of learning that is less effective so that learning becomes less optimal and lack of habituation to the use of dictionaries in the school environment.